EXAMINATION OF GRAM-NEGATIVE BACTERIA ON SALT-PACK CURED HIDES - (:unkn) unknown (AMER LEATHER CHEMISTS ASSOC, 2012)
Salt-pack curing is the most widely used method to preserve hides. However, inadequately applied salt-pack curing method supports the growth of proteolytic and lipolytic bacterial and archaeal flora which may reduce the quality of leather. Therefore, to examine the efficacy of salt-pack curing method applied to hides and to determine harmful microorganisms of the hides, Gram-negative bacteria on the salt-pack cured hides were isolated and identified and their proteolytic and lipolytic activities were investigated in the present study. Salt-pack cured hides examined were collected from different tanneries in Leather Organized Tannery Region, Tuzla-Istanbul, Turkey and 40% of the hides were imported from abroad. A total of 256 Gram-negative bacterial isolates containing 21 different genera (Acinetobacter, Aeromonas, Alcaligenes, Burkholderia, Citrobacter, Comamonas, Edwardsiella, Enterobacter, Escherichia, Hafnia, Klebsiella, Mannheimia, Pasteurella, Proteus, Pseudomonas, Salmonella, Serratia, Sphingomonas, Stenotrophomonas, Vibrio and Yersinia) and 46 different bacterial species were isolated and identified from the hide samples. The percentage of proteolytic, lipolytic and both proteolytic and lipolytic Gram-negative isolates on the hides were found as 68%, 52% and 43%, respectively. The most common Gram-negative genera on the salt-pack cured hides were Enterobacter (66), Pseudomonas (59) and Vibrio (32). These isolates showed both proteolytic and lipolytic activities in the highest number on the hides. As a conclusion, the hides contained a wide variety of destructive Gram-negative bacterial species originating from different environmental sources and traditional salt-pack curing method was not sufficient to inactivate these Gram-negative bacteria.
Keywords: CATTLE